ICT as a Resource for the Professional Training of Drivers. Education and Training School for Professional Drivers, Pelileo-Ecuador - Oleas-Orozco, José (2022)
This project is framed educational analysis in the education and training resources by professional drivers in Ecuador and use of ICT (Information and Communication Technologies). The study was developed in Escuela de Formación y Capacitación de Choferes Profesionales de Pelileo-Tungurahua. The study starts with a knowledge of reasons that cause traffic accidents on Ecuadorian roads, among which the conditions of the vehicles at the time of driving and foreseeable mechanical damage can be mentioned. The research consists of two moments, the first stage consists of an analysis of the learning resources that are used by the training centers in driving vehicles at a professional level, through a mixed methodology, with a quantitative section through surveys carried out on students. of the vehicle training center, to find out the level of interaction with ICTs, use of educational APPs and activity time on mobile devices. In the qualitative part, interviews were carried out with the instructors, from which it was possible to obtain information regarding teaching-learning techniques and resources, recurrent and necessary topics in the training of professional drivers. The second stage, based on the results of the first, determined the need to use technological tools for learning content for the training of drivers. Through the design of multimedia applications, content related to basic vehicle maintenance was configured, with multimedia elements (images, videos, animations, audio, etc.) contained in an APP for mobile devices. Subsequently, the application was tested on the students of the training center, to evaluate the effectiveness and capacity as a teaching-learning tool. The test obtained a positive perception of 99%, relevant content of 80%, usability of 90%.